A strategy for iron oxide nanoparticles to adhere to the neuronal membrane in the substantia nigra of mice. Issue 4 (3rd January 2020) - Han, Dong; Zhang, Baolin; Chong, Chuangang; Rong, Cuiping; Tan, Jie; Yang, Rusen
Abstract : FITC-SA/PEI-SPIONs attached to the dopaminergic neuronal membrane by means of streptavidin–biotin binding. Abstract : Effective attachment of magnetic nanoparticles to neuronal membranes has far-reaching significance in activating ion channels and treating neurodegenerative diseases. Superparamagnetic iron oxide nanoparticles (SPIONs) synthesized by the polyol pyrolysis method have the advantages of rich surface functional groups, excellent magnetic properties, controllable particle size and water dispersibility. We propose that perfusion of biotin into the targeted brain area should be initially performed because it tends to be adsorbed by cell membranes, followed by injection of streptavidin (SA)-modified SPIONs into the same area of the brain. By means of the strong binding force between SA and biotin, the SPIONs may subsequently adhere to the cell surfaces in the brain area. In this work, fluorescein isothiocyanate-streptavidin (FITC-SA) was modified on the surface of polyethylene imine (PEI)-SPIONs by the EDC–NHS method and stereotaxically injected into the biotin-supplemented substantia nigra of mice. The combination of fluorescence detection with transmission electron microscopy (TEM) confirmed that FITC-SA/PEI-SPIONs adhered to neuronal membranes in the substantia nigra of mice 24 h after injection. The results show that our strategy can promote the attachment of SPIONs to neuronal membranes.